Dynamic educational philosophy for learning technology management (Sociología y tecnociencia, 2023)
Notions such as STEAM education, computational thinking, gamification, and the manipulation of ICT (Artificial Intelligence, IoT, augmented reality, 3D printing or virtual reality), have appeared to configure what is known as Education 4.0. Under the Latin American context, and the economic, political, cultural and social situation of the countries that make up this geographical space, it is worth asking: to what extent has Education 4.0 been implemented, or some of its elements, unlike developed countries? Latin American educational systems, despite the global trend that seeks to assimilate the elements of this type of education, reflect a minority of countries possible to be classified as education 4.0, identifying the intelligible relationship between economic development and educational model.
Keywords: Gamificación; Industria 4.0; educación STEAM; tecnología de la información y comunicación; pensamiento computacional